The Business Model Canvas As A Solution of Innovation For A Small Business - Fitriani, Ratih (Universitas Pendidikan Indonesia, 2019)
In Indonesia, the government is very supportive in small micro businesses that in fact they have no experience in doing business. This study aims to develop businesses on a small to medium scale. MSMEs in Indonesia already have large groups with little capital. Producing it is done in the prosperity of society and will be able to sustain the family economy. People must compete to compete to produce products that can be accepted by consumers. With innovation can create opportunities that can compete in the industry. Product innovation by the quality of quality of materials requested to serve the industry. Based on the results of SWOT analysis should be developed for business planning, SMEs can create new innovations for the beginner businessman. Therefore, this study uses the methods used to model business canvas using qualitative methods to determine the business model of the canvas for beginners business. The design of the canvas business model is designed to map out, describe what indicators should be owned to build a business. Characteristics of the canvas business model are customer, distribution, value, resource, activity, cost and income. This paper aims to identify the strengths of the Canvas Business Model and more importantly SWOT's weakness to determine how much can be used to build a business model in appreciating the attributes of small business competition is innovation.